2017
DOI: 10.18632/oncotarget.20041
|View full text |Cite
|
Sign up to set email alerts
|

A ketogenic diet supplemented with medium-chain triglycerides enhances the anti-tumor and anti-angiogenic efficacy of chemotherapy on neuroblastoma xenografts in a CD1-nu mouse model

Abstract: Neuroblastoma (NB) is a pediatric malignancy characterized by a marked reduction in aerobic energy metabolism. Recent preclinical data indicate that targeting this metabolic phenotype by a ketogenic diet (KD), especially in combination with calorie restriction, slows tumor growth and enhances metronomic cyclophosphamide (CP) therapy of NB xenografts. Because calorie restriction would be contraindicated in most cancer patients, the aim of the present study was to optimize the KD such that the tumors are sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 92 publications
4
73
1
1
Order By: Relevance
“…Moreover, the decrease in insulin level that accompanies the indicated ketonemic conditions correlates with a decrease in insulin-like growth factors, which promotes the proliferation of cancer cells [76]. It was shown on neuroblastoma xenografts in a CD1-nu mouse model that a ketogenic diet consisting of fat (25% medium-chain triglycerides and 75% long-chain triglycerides) and carbohydrates + protein gave the same effective therapeutic effect against neuroblastoma as did the classical ketogenic diet combined with caloric restriction [77].…”
Section: Curbing Cancer Progression With Ketone Bodies/ketogenic Dietmentioning
confidence: 99%
“…Moreover, the decrease in insulin level that accompanies the indicated ketonemic conditions correlates with a decrease in insulin-like growth factors, which promotes the proliferation of cancer cells [76]. It was shown on neuroblastoma xenografts in a CD1-nu mouse model that a ketogenic diet consisting of fat (25% medium-chain triglycerides and 75% long-chain triglycerides) and carbohydrates + protein gave the same effective therapeutic effect against neuroblastoma as did the classical ketogenic diet combined with caloric restriction [77].…”
Section: Curbing Cancer Progression With Ketone Bodies/ketogenic Dietmentioning
confidence: 99%
“…KD is an 'umbrella term' used to describe high fat, low carbohydrate, adequate protein diets which promote the utilization of fat for energy, in the form of ketones. Initially hypothesized to work by exploiting the 'Warburg effect' [6][7][8][9], newer theories have proposed other mechanisms of action, with ketone bodies and medium chain triglyceride (MCT) fats playing a role in tumor metabolism, rather than or in addition to a reduction in glucose [10][11][12][13]. Animal models of glioma have shown that KD potentiates the effects of radiotherapy [14], reduce peri-tumoral edema [15] and reduce tumor angiogenesis [7].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…We sequenced a small customized panel (NB-mechanopanel) of speci c genes, with mutations previously described in NB related to cytoskeleton remodeling and extracellular matrix changes, and other genes related to NB and cancer in general (Table S2). In SK-N-BE(2) cell line and in all samples derived from it, we identi ed two mutations described as p.C135F in TP53 [45] and p.N755K in ATRX [46], de ned as pathogenic in the COSMIC database. The p.I1590 = and p.P1323L variants of COL11A1 (in 1p), and the intronic polymorphisms c.1680-9045C > G and c.54-20738C > T of DOCK8 (in 9p) were not detected in the majority of VN-KO tumors that had heterozigotic deletions of both chromosomal regions (1p-and 9p-), despite their presence in the rest of the samples, including in the 2D cultured cell line, with allelic frequency of approximately 0.4.…”
Section: Biotensegrity Had Impact In Single Nucleotide Mutationsmentioning
confidence: 99%